2022
DOI: 10.3390/ijerph192315594
|View full text |Cite
|
Sign up to set email alerts
|

‘This Is What the Colour Green Smells Like!’: Urban Forest Bathing Improved Adolescent Nature Connection and Wellbeing

Abstract: Background: Research suggests that an early connection with nature can benefit wellbeing into adulthood. However, there is less research assessing whether adolescents benefit from formal nature connection interventions such as forest bathing (slow mindful nature walks). This research aimed to assess whether an urban nature connection intervention (called ParkBathe) could improve adolescents’ nature connection and wellbeing. Method: In an experimental repeated measures design, 44 adolescents sampled opportunist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 41 publications
2
5
0
1
Order By: Relevance
“…Practicing forest bathing three times had a large effect size (Hedges' g = 1.0) and further increased the participants' mean mental well-being by two points to 56.3 ± 4.0. These results align with previous forest bathing research involving adult [2,8,[11][12][13][14][15] and adolescent [71] participants.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Practicing forest bathing three times had a large effect size (Hedges' g = 1.0) and further increased the participants' mean mental well-being by two points to 56.3 ± 4.0. These results align with previous forest bathing research involving adult [2,8,[11][12][13][14][15] and adolescent [71] participants.…”
Section: Discussionsupporting
confidence: 91%
“…Each stage is designed to create opportunities for embodiment, sensuality, and relationships [9,28]. This sequence of forest bathing, described later, includes many components that support practitioners in experiencing a healing connection with whatever natural environment they choose, although there is abundant evidence that other types of forest bathing practices provide well-being benefits [2,8,[11][12][13][14][15][49][50][51][52]71].…”
Section: The Practice Of Forest Bathingmentioning
confidence: 99%
“…With respect to NC, our study found high ratings of the NC indicator INS following a FB with an NCA session. This result is consistent with previous research that has found associations between forest bathing and high scores in nature connection [75,76]. Furthermore, and with reference to the correlation between NC and a low arousal positive effect, our results contribute to existing research showing that connecting with nature elicits low arousal positive emotions.…”
Section: Rating Emotional and Nature Connection Indicators Of Well-beingsupporting
confidence: 93%
“…Each study compared depression and anxiety ratings postintervention with those obtained prior to the intervention. Out of these six studies, five were rated as fair quality [28 ▪ ,29 ▪ ,30 ▪▪ ,31,32 ▪ ], and only one received a good quality rating [33 ▪ ]. Various interventions included passive exposure and specific activities (e.g., walking or cycling in a forest) within a designated natural environment.…”
Section: Resultsmentioning
confidence: 99%